ENHANCING ZEOLITE PERFORMANCE THROUGH AMINO MODIFICATION: A REVIEW OF METHODS AND CHARACTERIZATION - Salvira Permanaputri; Cucuk Evi Lusiani (Politeknik Negeri Malang, 2025)
The increase in CO2 emissions in Indonesia is primarily attributed to the expansion of the economy and ongoing industrialization, primarily driven by the operation of fossil fuel power plants. It is imperative to implement strategies aimed at reducing CO2 emissions in the industrial sector in order to effectively address Indonesia's pollution problems. An effective method involves utilizing adsorbents, specifically zeolites, to capture and convert CO2 into valuable fuels. In order to improve the adsorption of CO2, the zeolite is chemically modified by adding amine groups. The objective of this literature study is to examine the impact of adding amine groups into zeolite on CO2 adsorption. We collected various theories and data methods to compare the CO2 adsorption and characterization of modified zeolites. The characterization of the zeolites was determined using XRD, BET, and FTIR techniques. In general, the modification of zeolite with amines has a substantial effect on its properties, particularly on the surface area and volume porosity.